Pollen development, biology and function - Weryszko-Chmielewska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
The paper presents the role of pollen in multiplication of plants, discussing in particular the structure and function of certain parts of pollen. Pollen grains contain many different kinds of proteins, but even a small amount of them may cause allergic reactions. These proteins are localized within the cell wall and cytoplasm of pollen grains. Pollens are transported with the help of animals, wind and water. The author discusses different ways of migration of pollen grains taking into account their size and weight.